2014
DOI: 10.1371/journal.pone.0104134
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA Gene Survey of Microbial Communities in Winogradsky Columns

Abstract: A Winogradsky column is a clear glass or plastic column filled with enriched sediment. Over time, microbial communities in the sediment grow in a stratified ecosystem with an oxic top layer and anoxic sub-surface layers. Winogradsky columns have been used extensively to demonstrate microbial nutrient cycling and metabolic diversity in undergraduate microbiology labs. In this study, we used high-throughput 16s rRNA gene sequencing to investigate the microbial diversity of Winogradsky columns. Specifically, we t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 54 publications
2
35
0
Order By: Relevance
“…After 16 weeks the composition had again changed strikingly, with a resurgence in Proteobacteria (27 ± 9%) and Bacteroidetes (10 ± 7%), the emergence of Spirochaetes (10 ± 8%) and variable persistence of Firmicutes (35 ± 19%). These observations are similar to those of previous studies on Winogradsky column ecology which showed that Proteobacteria , Bacteroidetes and Firmicutes were the dominant phyla (Rundell et al ., ; Abbasian et al ., ), though the overall community composition was source sediment‐dependent (Pagaling et al ., ; Rundell et al ., ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…After 16 weeks the composition had again changed strikingly, with a resurgence in Proteobacteria (27 ± 9%) and Bacteroidetes (10 ± 7%), the emergence of Spirochaetes (10 ± 8%) and variable persistence of Firmicutes (35 ± 19%). These observations are similar to those of previous studies on Winogradsky column ecology which showed that Proteobacteria , Bacteroidetes and Firmicutes were the dominant phyla (Rundell et al ., ; Abbasian et al ., ), though the overall community composition was source sediment‐dependent (Pagaling et al ., ; Rundell et al ., ).…”
Section: Resultsmentioning
confidence: 98%
“…This makes it possible to perform replicate experiments on a scale that would be impossible for animals or plants. Here, we exploited these attributes to make a direct test of the reproducibility of microbial ecosystem development, using nutrient-cycling microcosms (Winogradsky columns) made from freshwater pond sediment and water (Rundell et al, 2014;Abbasian et al, 2015). The microbiology of the Winogradsky column is wellunderstood, with the key stages in its initial development being driven by anaerobic cellulose degradation and subsequent sulphate reduction (Rogan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial community heat map analysis (Rundell et al . ) and multiple‐sample similarity tree construction (weighted FastUnifrac) (Lozupone and Knight ) were used to compare differences and similarities between the three bacterial community structures (Fig. a).…”
Section: Resultsmentioning
confidence: 99%
“…This analysis confirmed that the bacterial communities were most similar between T25 and T37, as indicated by the T25 and T37 samples clustered together, while T4 was separate from the two other samples. Microbial community heat map analysis (Rundell et al 2014) and multiple-sample similarity tree construction (weighted FastUnifrac) (Lozupone and Knight 2005) were used to compare differences and similarities between the three bacterial community structures (Fig. 9a).…”
Section: Community Comparisonsmentioning
confidence: 99%
“…Secondly, we explore the use of -omics data in defining nutrients and cultivation conditions for Poribacteria and the addition of a sponge derived antibiotic (aeroplysinin-1). Lastly, we describe the first attempts to enrich a complex microbial community maintaining at least some metabolic interactions of the sponge microbiome in a stratified cultivation system based on the Winogradsky-column approach (Madigan et al, 2014;Rundell et al, 2014) and within Liquid-Solid cultures.…”
Section: Introductionmentioning
confidence: 99%